An Adaptive Time-Varying Impedance Controller for Manipulators - Liang, Xu; Su, Tingting; Zhang, Zhonghai; Zhang, Jie; Liu, Shengda; Zhao, Quanliang; Yuan, Junjie; Huang, Can; Zhao, Lei; He, Guangping (Frontiers in Neurorobotics, 2022)
Aiming at the situation that the structural parameters of general manipulators are uncertain, a time-varying impedance controller based on model reference adaptive control (MRAC) is proposed in this paper. The proposed controller does not need to use acceleration-based feedbacks or to measure external loads, and can tolerate considerable structure parameter errors. The global uniform asymptotic stability of the time-varying closed-loop system is analyzed, and a selection approach for control parameters is presented. It is demonstrated that, by using the suggested control parameter selection approach, the closed-loop system under the adaptive controller is equivalent to an existing result. The feasibility of the presented controller for general manipulators is demonstrated by some numerical simulations.